2016
DOI: 10.5114/reum.2016.58755
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis and polymorphisms of osteoprotegerin gene in postmenopausal women – a pilot study

Abstract: ObjectivesOsteoprotegerin (OPG) has an important role in bone remodeling, and it has been proposed that the OPG gene might be a candidate gene for osteoporosis predisposition. Several studies have already assessed the connection between OPG gene polymorphism and bone mineral density (BMD). In this study we wanted to analyze the association of two polymorphisms in the OPG gene with BMD and bone turnover markers in women with and without osteoporosis.Material and methodsIn 22 postmenopausal women with osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Finally, in a recent study of randomly selected 22 postmenopausal women and 59 women without osteoporosis, there was a trend for A163G polymorphism in terms of a positive correlation with higher bone loss. Furthermore, the results of their study indicated that a significantly greater number of women with osteoporosis had AG polymorphism compared to women without osteoporosis, while no significant difference was found in the prevalence of TT and GG polymorphisms between patients with and without osteoporosis (15). We also found similar results in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, in a recent study of randomly selected 22 postmenopausal women and 59 women without osteoporosis, there was a trend for A163G polymorphism in terms of a positive correlation with higher bone loss. Furthermore, the results of their study indicated that a significantly greater number of women with osteoporosis had AG polymorphism compared to women without osteoporosis, while no significant difference was found in the prevalence of TT and GG polymorphisms between patients with and without osteoporosis (15). We also found similar results in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Growing evidence suggest that OPG is among the most important candidate genes associated with the pathogenesis of osteoporosis (5,12). To date, several single nucleotide polymorphisms (SNPs) in OPG have been identified, including A163G, T245G, T950C and G1181C, which have been evaluated in terms of their relationship with osteoporosis and BMD (5,7,8,(13)(14)(15). Several genes among these have been assumed to influence BMD determination; however, the magnitude of impact and the exact role of these genes remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that osteoporosis and BMD are heritable ( 6 , 7 ), and >60 susceptible loci have been found to be associated with osteoporosis and BMD ( 6 ). Among these, polymorphisms of several genes have been found to be involved in PMOP, including tumor necrosis factor (TNF)-α, interleukin (IL)10, osteoprotegerin, estrogen receptor 1 gene, estrogen receptor α, cannabinoid receptor 2, vitamin D receptor gene and LDL receptor related protein 5 ( 8 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two meta-analysis study found G allele of the OPG 163A>G polymorphisms increased osteoporosis risk in Caucasians whereas allele C of the OPG 1181G>C decreased osteoporosis risk mainly in Asians (31,32). A pilot study by Cvijetic showed that postmenopausal women with osteoporosis had AG genotype (of the 163A>G) polymorphism more frequently than women without osteoporosis while the prevalence of TT and GG polymorphism between patients with and without osteoporosis was not significantly different (35). Langdahl et al (23) reported that in SNP 163A>G, G alleles were more commonly found in subjects with osteoporosis than normal.…”
Section: Discussionmentioning
confidence: 99%